Tank-Zapfsäule, verbunden mit einem Drucker zum Ausstellen der Quittung, um 1960
Wirtschaft;Industrie;Elektroindustrie;elektrotechnische Industrie;Elektromaschine Verkehr;Landverkehr;Strassenverkehr;Motorfahrzeug;Auto Verkehr;Landverkehr